Pengelolaan dan Dinamika Sampah di Desa Ulekan Kabupaten Karawang Di Tinjau Dari Peraturan Daerah Kabupaten Karawang Nomor 9 Tahun 2017 Tentang Pengelolaan Sampah - Reonaldy Saputra Hutgalung; Oci Senjaya (Wajah Hukum, 2021)
Waste problems in Indonesia will increase due to public awareness of serious waste problems. The problem of waste management is an issue that we must solve together in order to grow a sense of love and concern for a clean and healthy environment. The research method that we use is the empirical method by directly visiting the Karawang Environmental Office, by directly interviewing the head of the UPTD 1 DLHK (Karawang Environmental Service) namely Mr. Luki, asking about providing solutions and the government's own movement to the problem of the waste management process in Ulekan Village. in order to create a quality environment that is healthy and clean. Referring to the definition of waste and its types, it is necessary to handle and manage waste in a good way. Referring to information from the Department of Public Works of Semarang City (2008), waste management can be done with 3R waste management, namely: Reuse (Reuse), Reduce (Reduce), Recycle (Recycle). Given the increasing population growth every day, the waste produced by each citizen will increase and create problems regarding waste that accumulates and is scattered. This is exacerbated by inadequate places and locations for waste disposal, there is still a lack of public understanding of the benefits of waste. Various things have led to a decline in environmental quality which has a negative impact on the community.